2020
DOI: 10.1177/1756284820979165
|View full text |Cite
|
Sign up to set email alerts
|

The single-monitor trial: an embedded CADe system increased adenoma detection during colonoscopy: a prospective randomized study

Abstract: Background: Computer-aided detection (CADe) of colon polyps has been demonstrated to improve colon polyp and adenoma detection during colonoscopy by indicating the location of a given polyp on a parallel monitor. The aim of this study was to investigate whether embedding the CADe system into the primary colonoscopy monitor may serve to increase polyp and adenoma detection, without increasing physician fatigue level. Methods: Consecutive patients presenting for colonoscopies were prospectively randomized to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 35 publications
3
86
0
Order By: Relevance
“…Variations in practices have led to inconsistent reports on the frequency of FPs. The CADe-assisted detection of colon polyps has reported an average of 0.071 to 0.201 FPs per colonoscopy [ 4 , 5 , 6 , 7 , 8 , 14 ]. However, studies using FPs as the primary outcome reported an average of 26.3 to 27.3 FPs per colonoscopy, despite having extracted videos from the same RCT [ 5 ] or having used a similar CADe model to that of a previous RCT [ 7 ].…”
Section: Definition Of False Positivesmentioning
confidence: 99%
See 4 more Smart Citations
“…Variations in practices have led to inconsistent reports on the frequency of FPs. The CADe-assisted detection of colon polyps has reported an average of 0.071 to 0.201 FPs per colonoscopy [ 4 , 5 , 6 , 7 , 8 , 14 ]. However, studies using FPs as the primary outcome reported an average of 26.3 to 27.3 FPs per colonoscopy, despite having extracted videos from the same RCT [ 5 ] or having used a similar CADe model to that of a previous RCT [ 7 ].…”
Section: Definition Of False Positivesmentioning
confidence: 99%
“…Although the frequency of FPs was reported as per-colonoscopy, RCTs evaluating CADe systems did not employ the algorithm during insertion [ 4 , 6 , 7 , 8 , 14 ], and the post hoc analysis of videos for FPs invariably involved only the withdrawal phase [ 12 ]. It is conceivable that more FPs would be observed during insertion, where the bowel lumen is supposed to be kept minimally distended and the bowel contents have not yet been removed through cleaning.…”
Section: Definition Of False Positivesmentioning
confidence: 99%
See 3 more Smart Citations